PENJATUHAN SANKSI PIDANA DIBAWAH BATAS MINIMUM ANCAMAN HUKUMAN BAGI ANAK PELAKU TINDAK PIDANA NARKOTIKA - Amru Eryandi Siregar; Madiasa Ablisar; Mahmud Mulyadi; Marlina Marlina (USU LAW JOURNAL, 2017)
ABSTRACT Some of the reasons decided by penalties ½ (half) of the amount of the minimum sanction of imprisonment is based on Article 22 No. 3 of 1997 on Juvenile Justice, which is "Against the bad boy can only be dropped criminal or actions specified in this law". Then Article 23 Paragraph (1) Number 3Tahun 1997 on Juvenile Justice, which is "The penalties can be imposed on a bad boy is the subject of criminal and additional criminal, and Article 26, Paragraph (1) No. 3 of 1997, namely; "Imprisonment that can be imposed on juvenile delinquents referred to in Article 1 point 2 letter a maximum of ½ (one half) of a maximum imprisonment for adults". Of the three articles above, in fact there is no penalty associated settings ½ (half) of the amount of the minimum sanction of imprisonment and can be said to be the judge in this case making a legal breakthrough by the application of such penalties. The conclusion of this thesis, If the child committed the crime of Narcotics and charged article is based on Law No. 3 of 1997 on Juvenile Justice, the Judges under Article 24 of the Juvenile Court Act can: 1.Mengembalikan to a parent, guardian or person asuh.2.Menyerahkan to state for education, coaching and job training khusus.3.Menyerahkan to the Department of Social or Social Community Organizations engaged in coaching education and job training. Narcotics. Settings criminal offenses committed by minors under Law No. 35 Year 2009 on Narcotics in principle is not specifically regulated but arrangements will include Law No. 3 of 1997 on Juvenile Justice. It can be said Law No. 35 Year 2009 on Narcotics can not stand alone in terms of setting the crime of Narcotics committed by minors because of Act No. 3 of 1997 on Juvenile Justice is specific legislation relating to justice perpetrators of crimes committed by minors. That From the North Sumatra High Court Decision No. 369 / PID / 2013 / PT-MDN, Stabat District Court Decision No. 349 / PID.SUS.A / 2013 / PN.STB, Stabat District Court Decision No. 443 / PID.SUS. A / 2014 / PN.STB, Stabat District Court Decision No. 444 / PID.SUS.A / 2014 / PN-STB, Stabat District Court Decision No. 445 / PID.SUS.A / 2014 / PN.STB can be criticized especially those concerning the aggravating factors where the emphasis that the child should not know the drug, but in fact had known even used also to mengederkannya. Actually, such a case is not only seen from what has been done olehseorang children who do drug abusers, but should have a more visible is the background why the child did it, or in other words what factors cause them to do that (teaching causalitet). Keywords:         Imposition, Sanctions, Criminal, Below Minimum Limit, threats,           punishment, For Child Actors, Crime, Narcotics.